Effect of Age and Type of Cage (Close House and Open House) on Hen House, Feed Efficiency, Mortality and Livability of Laying hens - Fifi Susanti; Nining Haryuni; Lestariningsih Lestariningsih (Journal of Development Research, 2022)
The purpose of this study was to determine the effect of chicken age and type of cage on the hen house, feed efficiency, mortality and livability of laying hens. This research is an experimental study using 20000 laying hens. This study used a 2x5 factorial completely randomized design (CRD). The two factors were the age of the chickens (U) (30, 50 and 70 weeks) and the type of cage (K) (open house and close house). Based on the results of statistical analysis, it was found that the cage type had a very significant effect (p<0.01) on hen hpuse, feed efficiency, mortality and livability. Chicken age had a very significant effect (p<0.01) on hen house, feed efficiency and livability and significantly (p<0.05) on mortality. The interaction between the two has a very significant effect (p<0.01) on hen house, feed efficiency, mortality and livability. The average hen house obtained in this study ranged from 74.33-89.43%; feed efficiency 61.78-75.95%; mortality 0.01-0.35% and livability 81.83-98.33%. Based on the results of the study, it can be concluded that the interaction between laying hens age and cage type is closely related to hen house value, feed efficiency, mortality and livability. The best results were obtained from the interaction of chickens aged 30 weeks in a close house cage